2017
DOI: 10.1101/gad.298752.117
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of mouse neurogenesis by Pumilio proteins

Abstract: Despite extensive studies on mammalian neurogenesis, its post-transcriptional regulation remains under-explored. Here we report that neural-specific inactivation of two murine post-transcriptional regulators, Pumilio 1 (Pum1) and Pum2, severely reduced the number of neural stem cells (NSCs) in the postnatal dentate gyrus (DG), drastically increased perinatal apoptosis, altered DG cell composition, and impaired learning and memory. Consistently, the mutant DG neurospheres generated fewer NSCs with defects in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
157
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(166 citation statements)
references
References 75 publications
9
157
0
Order By: Relevance
“…Mammalian Pum orthologs have crucial, diverse roles in growth and development, gametogenesis, hematopoiesis, neurogenesis, behavior, motor function and memory formation (97)(98)(99)(100)(101)(102)(103)(104)(105)(106). Their dysfunction has now been linked to cancer, neurodegeneration, epilepsy, memory impairment, reduced fertility, and developmental defects in mammals (97,98,100,103,(107)(108)(109)(110)(111). Thus, we anticipate that further elucidation of Pum function will facilitate better understanding of its role in development and disease, and perhaps inform future therapeutic interventions.…”
Section: The Mechanistic Insights Into Pum-mediated Repression Also Hmentioning
confidence: 99%
“…Mammalian Pum orthologs have crucial, diverse roles in growth and development, gametogenesis, hematopoiesis, neurogenesis, behavior, motor function and memory formation (97)(98)(99)(100)(101)(102)(103)(104)(105)(106). Their dysfunction has now been linked to cancer, neurodegeneration, epilepsy, memory impairment, reduced fertility, and developmental defects in mammals (97,98,100,103,(107)(108)(109)(110)(111). Thus, we anticipate that further elucidation of Pum function will facilitate better understanding of its role in development and disease, and perhaps inform future therapeutic interventions.…”
Section: The Mechanistic Insights Into Pum-mediated Repression Also Hmentioning
confidence: 99%
“…It is not entirely unexpected that pumilios are in axonal regions. FMRP, which is known to interact with PUM2 (Zhang et al, 2017), is localized in axons during synaptogenesis (Parvin et al, 2019), so it is likely that other FMRP partners also exhibit axonal localization in higher organisms.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that molecules that regulate pre-synaptic transport and transmission are important for learning and associative memory formation (Arey et al, 2018;Kaletsky et al, 2016;Lakhina et al, 2015;Li et al, 2016). Furthermore, pumilio is an important regulator of long-term memory in Drosophila (Dubnau et al, 2003), and mammalian PUM1/2 regulate dendrite morphogenesis, synaptic function, neuronal excitability, and hippocampal neurogenesis (Siemen et al, 2011;Vessey et al, 2010;Zhang et al, 2017). We therefore assessed the role of presynaptic pufs in positive olfactory associative memory, in which worms form a positive association with the neutral odorant butanone after pairing with food.…”
Section: Elegans Pufs Are Both Necessary Memory Components and Memmentioning
confidence: 99%
“…∆GWT is the affinity for the consensus sequence. (Bohn et al, 2018;Campbell et al, 2012;Campbell et al, 2014;Chen et al, 2012;Dominguez et al, 2018;Elemento et al, 2007;Fazlollahi et al, 2014;Foat et al, 2005;Francischini and Quaggio, 2009;Galgano et al, 2008;Gerber et al, 2004;Gerber et al, 2006;Hafner et al, 2010;Hogan et al, 2015;Jiang et al, 2010;Kershaw et al, 2015;Klass, 2013;Lapointe et al, 2015;Leibovich and Yakhini, 2012;Morris et al, 2008;Opperman et al, 2005;Rabani et al, 2008;Ray et al, 2013;Riordan et al, 2011;Sun et al, 2016;Wilinski et al, 2017;Zhang and Muench, 2015;Zhang et al, 2017). (B) RNA libraries used in this study.…”
Section: Figure 1 Quantitative High-throughput Measurements Of Rna Bmentioning
confidence: 99%